Notice of Retraction Succesive Co-Channel Interference Cancellation - Farzad Moazzami (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2015)
Notice of Retraction-----------------------------------------------------------------------After careful and considered review of the content of this paper by a duly constituted expert committee, this paper has been found to be in violation of IAES's Publication Principles.We hereby retract the content of this paper. Reasonable effort should be made to remove all past references to this paper.The presenting author of this paper has the option to appeal this decision by contacting ijeei.iaes@gmail.com.-----------------------------------------------------------------------In this work, a successive four-stage interference cancellation model to unwrap and remove two co-channel interference signals is introduced and successfully tested. This model utilizes the second order statistics of the co-channel interference signals in an interference limited communication environment for interference cancelation. In this model, interferers and the signal of interest (SOI) are considered as multiple inputs of a multiple-input multiple-output (MIMO) system. Therefore, MIMO equalizers and blind MIMO channel estimator are employed for the corresponding tasks.  At any stage of equalization in this model, a single signal is equalized and recovered. Later, a replica of the captured signal is cancelled from the received signal mixture. The remaining signal is fed to the next stage for equalization. The benefit of using this scheme is mainly improving the quality of the SOI by re-equalizing after interferers are completely removed. In the results section, 16 dB interference cancellation gain is shown where interferers are as strong as signal (SIR=0) and SNR is 30 dB. A Rayleigh fading (iid) channel is used for simulation.